TEACHING ACCOUNTING BY PRINCIPLE AND CONVENTION. - Henke, Emerson (The Accounting Review, 1958)
Abstract Patterns of teaching in many areas of education today seem to emphasize learning by memorization. This often is initiated by the presentation of certain data in lecture form. The student is then expected to return the same data to the teacher in written form at examination time. Since almost all students are likely to be subjected to this type of learning process during a large portion of their high school and some of their college courses, the accounting teacher usually faces the difficult task of remolding the student's learning habits to encourage him to develop the reasoning and thinking abilities so necessary to the accountant. The teacher has to develop his presentation and examinations in such a way that the student is forced into the new pattern of learning. One means of aiding this development is to organize class data into a logical, related body of knowledge. Points which need to be memorized or learned out of relationship with any other material should be set out clearly and designated as such. The elementary accounting student needs to master certain definitions and the accounting equation at the outset. The student can be shown how these terms relate to business operations. This establishes a common basis for communication relative to the information to be presented.